NILAI GIZI MAKRO, ANTIOKSIDAN DAN SIFAT SENSORI SARI KEDELA DENGAN PENAMBAHAN FILTRAT KULIT BUAH NAGA MERAH - Evriana Dwi Fairuzia (Ghidza Media Jurnal, 2021)
The purpose of this study was to determine the effect concentration and addition of red dragon fruit peel filtrate with different formulations on the macro nutritional value and sensory properties of soybean juice. The research method used an experimental design with a completely randomized design (CRD) consist of 3 formulas (F1, F2, and F3) and 1 control formula (F0). The results of the organoleptic test were carried out by the Friedman and the Ducan test. Data on macro nutrient and antioxidant levels were analyzed using the One Way Anova test followed by the LSD test. The chemical test results of macro nutrients and antioxidants showed a significant effect between the formula (0.00 <0.05) and the macro nutrients F0, F1, F2, F3, namely carbohydrates 10.18 g, 10.19 g, 10.10 g, 10.01g, protein 8.35 g, 8.32 g, 8.28 g, 8.25 g, fat 3.14 g , 3.10 g, 3.06 g, 3.00 g, antioxidants 34.04 µg/mL, 30.06 µg/mL, 25.10 µg/mL, 17.87 µg/mL. Organoleptic results (F0, F1, F2, F3) color preferences 2.49, 2.91, 3.53, 3.57, taste 2.89, 3.00, 3.51, 2.96, and aroma 2.34, 2.77, 3.38, 3.17, there is a significant influence between the formula and the Chi-Square value Asym.sig <0.05 and the best formula is obtained, namely F3.